2017
DOI: 10.3389/fmars.2016.00288
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Residency of Green and Loggerhead Sea Turtles Using Coastal Reef Habitats in Southern Mozambique

Abstract: Sea turtles spend the majority of their immature and adult lives in foraging grounds, yet few studies have examined their abundance and condition in these areas when compared to more accessible nesting beach habitats. Here, a 5-year dive log, photo-identification (photo-ID) and surface encounter datasets were used to investigate the abundance, individual movements and distribution of sea turtles along 40 km of coastal reefs in southern Mozambique. A generalized linear model (GLM) was constructed with turtle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 67 publications
1
12
0
2
Order By: Relevance
“…Standora et al 1984). Perception and availability bias may also affect detectability of turtles as highlighted by Williams et al (2017). Future work should standardise data collection protocols, including visibility (to ensure unbiased detection of turtles in-water) and in situ temperature logging to fully elucidate the daily activity of turtles at the study site if accurate estimates of abundance are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Standora et al 1984). Perception and availability bias may also affect detectability of turtles as highlighted by Williams et al (2017). Future work should standardise data collection protocols, including visibility (to ensure unbiased detection of turtles in-water) and in situ temperature logging to fully elucidate the daily activity of turtles at the study site if accurate estimates of abundance are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other minor nesting sites are located on continental islands and shores on the coast of Madagascar and East Africa (Bourjea, Ciccione, & Ratsimbazafy, ; Garnier et al, ). Seagrass beds, the main component of adult green turtle diet (Bjorndal, ), extend almost continuously over the east African coast from Mozambique to Somalia and over the western coast of Madagascar (Figure ; Gullström et al, ), and foraging green turtles are observed in all countries of the SWIO hosting seagrass beds (Ballorain et al, ; Fulanda et al, ; Muir, ; Okemwa, Nzuki, & Mueni, ; Williams, Pierce, Rohner, Fuentes, & Hamann, ). A tracking study (Dalleau, ) demonstrated that (a) the northern part of the Mozambique Channel is a major oceanic migration corridor for postnesting green turtles capable to migrate thousands of kilometers, (b) coastal grounds of East Africa and West Madagascar are important foraging sites and migration corridors, (c) turtles from the SWIO nesting sites make extensive use of available foraging habitats of the whole region, and (d) foraging grounds are used by turtles originating from different rookeries of the SWIO.…”
Section: Introductionmentioning
confidence: 99%
“…Other minor nesting sites are located on continental islands and shores on the coast of Madagascar and East Africa (Bourjea, Ciccione, & Ratsimbazafy, 2006;Garnier et al, 2012). Seagrass beds, the main component of adult green turtle diet (Bjorndal, 1997), extend almost continuously over the east African coast from Mozambique to Somalia and over the western coast of Madagascar (Figure 2; Gullström et al, 2002), and foraging green turtles are observed in all countries of the SWIO hosting seagrass beds (Ballorain et al, 2010;Fulanda et al, 2007;Muir, 2005;Okemwa, Nzuki, & Mueni, 2004;Williams, Pierce, Rohner, Fuentes, & Hamann, 2017). A tracking study (Dalleau, 2013) Threats are highly variable in the SWIO region, which is bordered by countries and provinces of heterogeneous economic levels.…”
Section: Introductionmentioning
confidence: 99%
“…sites!can!be!influenced!by!underwater!visibility! (Williams!et!al.,!2017),!so!observers!estimated! horizontal!visibility!on!each!dive.!Water!temperature!can!influence!mobulid!sightings!(Jaine!…”
Section: Surveys!mentioning
confidence: 99%
“…need!to!swim!to!the!surface!to!breathe! (Williams!et!al.,!2017).!Manta!rays,!in!contrast,!are! generally!…”
Section: !!mentioning
confidence: 99%